Heavy metals in the environment : using wetlands for their removal - Odum, Howard T., 1924- (Lewis Publishers, 2000)
Much of the convenience of modern life resides in sheet metal, the cowling shield of most machines and appliances. However, the load that this takes off human shoulders has to be carried elsewhere, and the Earth has borne the burden. Many of us woke up to the environmental cost when over a century of industrialization finally surpassed the capacity of nature to assimilate it. International in scope, Heavy Metals in the Environment: Using Wetlands for Their Removal discusses wetland functions and heavy metal contamination. It addresses such questions as: Can systems powered by sunlight handle to.
Keywords: Heavy metals -- Environmental aspects.; Lead -- Environmental aspects.; Wetland ecology.; Bioremediation.; Ecological engineering.; elektronické knihy; electronic books